Biological pretreatment of corn straw for enhancing degradation efficiency and biogas production. Issue 1 (1st January 2020) - Li, Panpan; He, Chao; Li, Gang; Ding, Pan; Lan, Mingming; Gao, Zan; Jiao, Youzhou
ABSTRACT: In order to explore the effect of pretreatment on corn straw degradation and biogas production, corn straw was pretreated with mixed microbes and composting at 30°C for 14 days. The characteristics of material were measured and analyzed in the pretreatment process. Then, the pretreated and untreated corn straw was digested by anaerobic fermentation. Gas production and methane content of corn straw were analyzed. The results showed that the biological pretreatment process with mixed microbes could accelerate the degradation rate of straw and increase the degradation efficiency of lignin. The pH value of material was more stable, and the content of organic matter in the material was higher in the pretreatment process of corn straw with mixed microbes. The Scanning Electron Microscope (SEM) images showed that the structure of the lignocellulose was changed by mixed microbes, increasing the exposed area of cellulose and hemicellulose, which was beneficial to improve the utilization efficiency of straw. The degradation rates of hemicellulose, cellulose and lignin were 44.4%, 34.9% and 39.2%, respectively, after the pretreatment process with mixed microbes. Pretreatment was more helpful to increase the methane content in the anaerobic fermentation process of corn straw pretreated with mixed microbes, and could also shorten the fermentation period. Graphical abstract 1: